Hitchcock Truffaut [videorecording (DVD)] - Jones, Kent, 1960-; Hitchcock, Alfred, 1899-1980; Truffaut, François (Universal Studios Home Entertainment, 2016)
In 1962 Hitchcock and Truffaut locked themselves away in Hollywood for a week to excavate the secrets behind the mise-en-scene in cinema. Based on the original recordings of this meeting, used to produce the mythical book, Hitchcock/Truffaut-this film illustrates the greatest cinema lesson of all time and plummets us into the world of the creator of Psycho, The Birds, and Vertigo. Hitchcock's incredibly modern art is elucidated and explained by today's leading filmmakers. Includes bonus materials.